Northern Political Development and India: A Study on India-Sri Lanka Relationship - Ganeshalingam, K.T. (University of Jaffna, 2014)
In the history of Independent Sri Lanka there has been a conflicting relationship between India and Sri Lanka. Initially Sri Lanka maintained relationship with western countries, such as Britain and US and distanced itself from India. At present it has established relationship with China and has conflicting relationship with India. During the Sri Lankan President’s visit a number of agreements were reached and contracts signed, relating to Northern reconstruction activities specially railways, and cooperation in various sectors of the economy with India. Concessionary credit lines were extended by India for some projects. There will be infrastructure improvements for Sri Lanka, while Indian companies will benefit from the contracts.
Keywords: Relationship; Geo-politics; Infrastructure